Deep brain stimulation in PD: risk of complications, morbidity, and hospitalizations: a systematic review - Olson, Markey C.; Shill, Holly; Ponce, Francisco; Aslam, Sana (Frontiers in Aging Neuroscience, 2023)
Introduction Parkinson’s disease (PD) is a progressive and debilitating neurological disorder. While dopaminergic medication improves PD symptoms, continued management is complicated by continued symptom progression, increasing medication fluctuations, and medication-related dyskinesia. Deep brain stimulation (DBS) surgery is a well-accepted and widespread treatment often utilized to address these symptoms in advanced PD. However, DBS may also lead to complications requiring hospitalization. In addition, patients with PD and DBS may have specialized care needs during hospitalization. Methods This systematic review seeks to characterize the complications and risk of hospitalization following DBS surgery. Patient risk factors and modifications to DBS surgical techniques that may affect surgical risk are also discussed. Results It is found that, when candidates are carefully screened, DBS is a relatively low-risk procedure, but rate of hospitalization is somewhat increased for DBS patients. Discussion More research is needed to determine the relative influence of more advanced disease vs. DBS itself in increased rate of hospitalization, but education about DBS and PD is important to insure effective patient care within the hospital.